The capability approach and well-being measurement for public policy - Alkire, S (Oxford University Press, 2016)
This chapter presents Sen’s capability approach as a framework for well-being measurement with powerful and ongoing relevance to current work on measuring well-being in order to guide public policy. It discusses how preferences and values inform the relative weights across capabilities, then draws readers’ attention to measurement properties of multidimensional measures that have proven to be policy relevant in poverty reduction. It presents a dual-cutoff counting methodology that satisfies these properties and outlines the assumptions that must be fulfilled in order to interpret ensuing indices as measuring capability poverty. It then discusses Bhutan’s innovative extension of this methodology in the Gross National Happiness Index and reflects upon whether it might be suited to other contexts. It closes by responding at some length to relevant material in other Handbook chapters.